Nauczanie aktywizujące w dydaktyce literatury okresu międzywojennego = Activating Teaching in the Interwar Period Didactics - Łojek, Mieczysław (1930-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article presents the tendency of literature teachers (between the years of 1918-1939) to work out such types of methods which would effectively stimulate the pupils (from elementary and secondary schools) to creative and intellectual work during the school lessons as well as at home.
Keywords: dydaktyka literatury; literatura polska - nauczanie - 1918-1939; nauczanie aktywizujące